(untitled) (GYMNASIUM, 2017)
The purpose of this study is to investigate young adults ‘career adapt-abilities with a view to various socio-demographic variables in the socio-cultural context of young adults in Turkey. The survey data were collected through a structured questionnaire consisting of a personal information form and career-related questions, and the Career Adapt-Abilities Scale (CAAS) developed by Savickas and Porfeli, 2012, and adapted into Turkish by Kanten (2012). The findings of the study corroborated the significance of miscellaneous demographic variables in accounting for the variability in young adults ‘career adapt-abilities. The most robust predictors of overall career adapt-abilities are the existence of a future career plan, and conscious choice of department (p< .05). Previous experience contributes to boosting young adults’ confidence. Gender, income, hometown, and future vocational aspirations to practice in the same field as one’s studies do not significantly predict overall career adaptability.